Research Progress on Processing Technology, Components, Microbial Diversity and Bioactivities of Pickled Tea - Haiyan LI; Cheng LUO; Yao LI; Fuyi WANG; Jinping ZHOU; Qiuye LIN (Shipin gongye ke-ji, 2023)
Pickled tea is prepared from the leaves of Camellia sinensisa with a microbial fermentation process under an anaerobic condition after fixation followed by drying and mainly found in Yunnan of China, Thailand, Myanmar, Laos and Japan. Unlike other post-fermented teas such as Pu'erh tea and dark tea, lactic acid bacteria are the dominant microorganisms of pickled tea, bestowing pickled tea with unique flavor characteristics and functional activities. Pickled tea has gaining increasing attention as a novel tea product fermented with lactic acid bacteria. This paper mainly reviews the production process, microbial diversity and nutritional and chemical composition of pickled tea prepared in different regions, as well as the its bioactivity of including antioxidant, antibacterial and regulatory metabolic syndrome, in order to provide a scientific theoretical basis for the in-depth research, development, inheritance and protection of pickled tea. The problems of probiotic resource, its quality stability, and standard processing of pickled tea are prospected, providing reference for further research of this tea.